Double Blinded Comparative Study of Bupivacaine with and without Dexamethasone in Supraclavicular Brachial Plexus Block - Muhammad Adnan Khan, Robina Bangash, Imran ul Haq, Aqsa Saleema, Khayyam Farid, Tanzeela Firdous, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Through the use of bupivacaine-induced brachial plexus blocking, it is possible to achieve high levels of anaesthesia and analgesia for surgical procedures. When dexamethasone was given to bupivacaine as an additive, the anaesthesia and analgesia lasted significantly longer in the patients who participated in the study. Aim: To study sensory and motor blockade, as well as the duration of postoperative analgesia and the duration of postoperative pain relief. Methods: We were able to enrol 60 patients in the experiment after they were approved by the Institutional Ethical Committee and provided written informed consent to participate. ASA I and II patients, ranging in age from 18 to 60 years old, who had undergone elective surgery on their upper extremities were included in this study. They were separated into two groups of almost equal size.. Results: The mean age in group 1 was 42.6 years with 13.6 SD whereas in group 2 mean age was 37.8 years with 12.5 SD. In group 1 mean weight was 61.7 kgs with 5.9 SD whereas in group 2 the mean weight was 58.2 kgs with 4.8 SD. The descriptive analysis of group 1 and group 2 showed that the mean pulse rate with SD was 83 ± 6.5 and 84 ± 7.2 respectively. While the systolic BP was recorded as 122 and 126 for groups 1 and 2 the standard deviation in this case was 7.8 and 6.4 respectively. Diastolic blood pressure for group 1 was 75 ± 8.2 SD and for group 2 it was recorded as 78 ± 7.9 SD. The analysis of SPO2 for group 1 was 97.3 ± 1.4 SD while group 2 showed 97.5 ± 1.1 SD as mean and SD values. For group 1 the onset of motor block ( minutes) was 3.8 ± 0.8 SD and for group 2 it was 17.5 ± 2.3 SD. Onset of sensory block ( minute) for group 1 was 7.2 ± 1.5 SD and for group it was 15.6 ± 1.6 SD. Conclusion: The addition of 15 millilitres of 0.5% bupivacaine to 15 millilitres of dexamethasone significantly accelerates the onset of sensory and motor blockage in the patient. It has been demonstrated to significantly increase the duration of sensory and motor blockage as well as analgesia. It has been demonstrated that dexamethasone adjuvant is completely safe and has no negative effects when used in the brachial plexus block.